PENEGAKAN HUKUM TERHADAP TINDAK PIDANAMENGHALANG-HALANGI AKTIVITAS SERIKAT PEKERJA/BURUH - Muhamad Sobri (2020)
Legal problems in both the formulation policy and the application of the law to cases of violations against workers are often in the spotlight. The purpose of this study is to find out how criminal law policy and its application both now and in the future in providing protection for the right to freedom of association for workers / laborers. This research method uses the normative judicial approach which is to examine the aspects of the formulation of legal policies and their application to criminal acts to obstruct trade unions. The data source uses primary, secondary and tertiary legal materials and qualitative and argumentative descriptive analysis methods. The results of the legal study explain: 1) The formulation of criminal law policy in Indonesia in protecting the right to freedom of association has been regulated in Law Number 21 of 2000 concerning Trade Unions / Labor Unions, where the Act guarantees workers / laborers to associate, gather and issue opinions as guaranteed in the international covenant on human rights; 2) The application of the law on Trade Union Laws has not been in favor of workers / laborers, this is because of differences in interests and roles assumed by both workers and employers. 3) There has not yet been a draft law that will regulate the more complex protection of freedom of association, the concept of the 2012 Criminal Code does not include the concept of criminal acts against labor rights or criminnal acts in the labor field. In addition, in criminal acts against Human Rights, it also does not include criminal offenses or the imposition of freedom of association, which in fact is the right of association as part of Human Rights. In order for the legal function to work as a legal institution in the community, it is necessary to have good will, firmness and fairness from the legal apparatus in implementing the laws, especially the Trade Union Law.